The (beauty of the) foolishness of God - Brouwer, Rein (Stellenbosch Theological Journal, 2019)
"The gospel is foolishness. Preaching is folly. Preachers are fools." This is the refrain throughout Johan Cilliers' and Charles Campbell's inspiring and unsettling book on homiletics. As the quote indicates, the authors connect the folly and foolishness to the gospel and to the preaching preacher. They invoke all kinds of fools, clowns, tricksters and jesters, including Jesus, to explain the meaning of "the folly of the cross", as Paul suggests in 1 Corinthians 1:18-25. However, Cilliers and Campbell do not so much address the implications of the folly of God, or, to put it in a different way, the folly that God is. Whenever they relate the foolishness to God, they refer to paradoxical phrases like "powerful weakness," or "different aesthetics," or the "terrible beauty" of the cross. They assume that an omnipotent God who is at the same time powerless and mocked at the cross is the ultimate figure of foolishness. Still, this vulnerable God remains in power, somehow. Resurrection guarantees triumph after all. In his The Folly of God (A Theology of the Unconditional, Salem/Oregon, Polebridge Press 2016), Jack Caputo, however, digs theologically deeper when it comes to what is going on in the name (of)"God". Caputo interprets the Pauline rhetoric on the folly of the cross in a more radical manner. He "weakens" the folly of God into an insistent call that we give existence in works of mercy. In Caputo's weak theology there is no ultimate winning God, despite the foolishness of the cross. Because, we do not know what is coming at us when we pray for God's kingdom. It might be beauty, even the beauty of folly, but it might also be a threat. That is the risk we take when putting our faith in the folly of God. This contribution intends to construct a dialogue between Cilliers and Caputo about the hermeneutics of 1 Corinthians 1:18-25 and its implications for understanding the folly of God.